Forensic pharmacology: An important and evolving subspecialty needs recognition in India - Harshad Onkarrao Malve (Wolters Kluwer Medknow Publications, 2016)
With training in pharmacology, a pharmacologist has an expert knowledge as well as working experience in the subjects of therapeutics, pharmacokinetics, and toxicology along with exposure to subjects such as forensic medicine during the medical education. All these knowledge domains can be applied and act as an interface to the forensic situations. The skills and expertise of a forensic pharmacologist can be useful in a large and diverse number of legal cases. With an ever increasing incidence of criminal and civil cases in India, the development and inclusion of forensic pharmacologist in the judicial system of India are the need of the hour. The research in pharmacology has witnessed great technological advancement that allows it to expand its scope beyond the domain of therapeutics, thus enabling Indian pharmacologists to explore the niche area of Forensic Pharmacology. Differing pharmacokinetics and pharmacodynamics of drugs in living and dead, drug interactions, abuse of drugs, personal injury or death due to drug exposure leading to medico-legal issues, environmental exposure to chemicals, and doping and forensic pharmacovigilance are the diverse aspects of Forensic Pharmacology.